2019
DOI: 10.1111/all.13991
|View full text |Cite
|
Sign up to set email alerts
|

PAG1 limits allergen‐induced type 2 inflammation in the murine lung

Abstract: Background Phosphoprotein associated with glycosphingolipid‐enriched microdomains 1 (PAG1) is a transmembrane adaptor protein that affects immune receptor signaling in T and B cells. Evidence from genome‐wide association studies of asthma suggests that genetic variants that regulate the expression of PAG1 are associated with asthma risk. However, it is not known whether PAG1 expression is causally related to asthma pathophysiology. Here, we investigated the role of PAG1 in a preclinical mouse model of house du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…Genetic variants in PAG1 were associated with asthma risk. PAG1 deficiency increased Th2 differentiation and favoured allergic sensitization 39 . Acid sphingomyelinase, a key regulator of sphingosine‐1‐phosphate pathway, promotes Th1 immunity in the airways.…”
Section: Asthma Pathophysiological Mechanismsmentioning
confidence: 99%
“…Genetic variants in PAG1 were associated with asthma risk. PAG1 deficiency increased Th2 differentiation and favoured allergic sensitization 39 . Acid sphingomyelinase, a key regulator of sphingosine‐1‐phosphate pathway, promotes Th1 immunity in the airways.…”
Section: Asthma Pathophysiological Mechanismsmentioning
confidence: 99%
“…Specifically, ILC2s secreted less type 2 cytokines in the early stage of influenza-induced acute exacerbation, and became the main source after virus clearance, while T cells showed increased production of IL-4 and IL-5 in the early stage [ 99 ]. It is easy to sensitize and aggravate the degree of asthma by promoting ILC2s amplification and Th2 differentiation [ 100 ]. Blocking T cell activation and Treg inhibition and promoting the increase of ILC2s could lead to severe Th2 immune response and airway inflammation [ 17 ].…”
Section: Crosstalk Between Ilc2s and Cd4 + T Cells...mentioning
confidence: 99%
“…Finally, PAG1, which affected immune receptor signaling in T and B cells, was up-regulated and limited the inflammation effect. Indeed, Ullah et al demonstrated that the PAG1 deficiency predisposed toward allergic sensitization and airways inflammation [ 62 ]. The results of gene up-regulation in BM-MSCs expanded inside the Nichoid, in agreement with the above-reported studies, suggest the improvement of the cells’ anti-inflammatory effects, possibly potentiating the therapeutic outcome of BM-MSCs.…”
Section: Discussionmentioning
confidence: 99%